2012
DOI: 10.1164/rccm.201201-0027oc
|View full text |Cite
|
Sign up to set email alerts
|

Airway Epithelial miRNA Expression Is Altered in Asthma

Abstract: Rationale: Changes in airway epithelial cell differentiation, driven in part by IL-13, are important in asthma. Micro-RNAs (miRNAs) regulate cell differentiation in many systems and could contribute to epithelial abnormalities in asthma. Objectives: To determine whether airway epithelial miRNA expression is altered in asthma and identify IL-13-regulated miRNAs. Methods:We used miRNA microarrays to analyze bronchial epithelial brushings from 16 steroid-naive subjects with asthma before and after inhaled cortico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
264
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(280 citation statements)
references
References 35 publications
10
264
4
2
Order By: Relevance
“…Pathway analysis of differentially expressed miRNAs belonged to JAK-STAT signaling, cytokine network, and cytokine and inflammatory response 13 . Let-7a was also found to be reduced in the airway epithelial cells 12 and serum 15 of asthma patients. Thus, reduced expression of let-7a in bronchial biopsies from patients with severe asthma is consistent with the findings of other studies 3,[10][11][12][13][14][15]19,25 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Pathway analysis of differentially expressed miRNAs belonged to JAK-STAT signaling, cytokine network, and cytokine and inflammatory response 13 . Let-7a was also found to be reduced in the airway epithelial cells 12 and serum 15 of asthma patients. Thus, reduced expression of let-7a in bronchial biopsies from patients with severe asthma is consistent with the findings of other studies 3,[10][11][12][13][14][15]19,25 .…”
Section: Discussionmentioning
confidence: 89%
“…However, the data on miRNA expression in the lungs of human subjects with asthma are still scarce. Several miRNAs, such as let7a, miR-21, and miR-223, have been shown to have a role in airway inflammation, T H 1/T H 2 polarization, and eosinophil development either directly or indirectly repress the translation of several crucial factors, and were shown to be differentially expressed in asthma 3,4,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . In the present study we analyzed the expression of three miRNAs (let-7a, miR-21, and miR-223) in bronchial biopsy samples from patients with mild and severe asthma and non-asthmatic controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one might also ask whether these miRNAs can serve as biomarkers of asthma endotypes. Using a similar approach to that which we employed for assessment of mRNA expression in airway epithelial cells, we performed companion experiments with bronchial epithelial cells in vitro and found that IL-13 had significant effects on bronchial epithelial miRNA expression and that several of these changes recapitulated the differences between asthma and health that we observed in our human studies (33). One finding that we have focused on in subsequent work is consistent repression of four members of the miR-34/449 family (miR-34c-5p, miR34c-5p, miR-449a, and miR-449b-5p) both in vivo in asthma and in vitro by IL-13.…”
Section: Airway Epithelial Micrornas As Endotypic Markersmentioning
confidence: 97%
“…More recently we have observed that microRNAs (miRNAs) are also highly differentially expressed in the airway epithelium of subjects with asthma as compared with healthy control subjects (33). miRNAs are approximately 22-nucleotide RNAs that promote mRNA degradation (34) or inhibit translation (35), by binding with at least partial complementarity to the 39 untranslated region of target mRNAs.…”
Section: Airway Epithelial Micrornas As Endotypic Markersmentioning
confidence: 99%